Separating time-frequency sources from time-domain convolutive mixtures using non-negative matrix factorization - Leglaive, Simon; Badeau, Roland; Richard, Gael (IEEE Workshop on Applications of Signal Processing to Audio and Acoustics : proceedings, 2017)
This paper addresses the problem of under-determined audio source separation in multichannel reverberant mixtures. We target a semiblind scenario assuming that the mixing filters are known. Source separation is performed from the time-domain mixture signals in order to accurately model the convolutive mixing process. The source signals are however modeled as latent variables in a time-frequency domain. In a previous paper we proposed to use the modified discrete cosine transform. The present paper generalizes the method to the use of the odd-frequency short-time Fourier transform. In this domain, the source coefficients are modeled as centered complex Gaussian random variables whose variances are structured by means of a non-negative matrix factorization model. The inference procedure relies on a variational expectation-maximization algorithm. In the experiments we discuss the choice of the source representation and we show that the proposed approach outperforms two methods from the literature.